Contour variations and acoustic characteristics of whistle sounds emitted by Pacific white‐sided dolphins in shallow coastal waters of the Sea of Japan. Issue 3 (11th December 2021) - Matsushiro, Marin; Nakamura, Misato; Chayahara, Yuko; Kooriyama, Takanori
Abstract: Pacific white‐sided dolphins, Lagenorhynchus obliquidens (PWSDs), migrate along the coast of Japan. PWSDs rarely emit whistles, instead utilizing pulses, unlike many other delphinid species that frequently emit whistle sounds. In the present study, we aimed to clarify the acoustic characteristics and repertoire of the whistle of PWSDs, which have not been reported so far. We analyzed PWSD whistle sound systems (e.g., acoustic parameters and contours) during boat surveys and using passive acoustic monitoring in shallow coastal waters in the northern Sea of Japan. PWSDs in Shakotan rarely emitted whistles, while the burst pulse frequently was as reported in previous studies in other waters. The PWSD whistle vocalization rates were higher during traveling than during foraging. The frequency and duration of their whistles did not appear to change between behaviors. Although complex multiloop whistles were not recorded, whistle contours were classified into seven types. Whistles are often recorded intensively in a short period as a sequence or bout. Considering the extremely low whistle vocalization rates, dolphins may choose whistles instead of pulsed sounds in limited contexts. Our results shed light on the differences in whistle sound usage within odontocete species.